Tubulin and Tubulin Posttranslational Modifications in Alzheimer’s Disease and Vascular Dementia - Santiago-Mujika, Estibaliz; Luthi-Carter, Ruth; Giorgini, Flaviano; Kalaria, Raj N.; Mukaetova-Ladinska, Elizabeta B. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) and vascular dementia (VaD) are the two most common forms of dementia in older people. Although these two dementia types differ in their aetiology, they share many pathophysiological and morphological features, including neuronal loss, which is associated with the microtubule (MT) destabilisation. Stabilisation of MTs is achieved in different ways: through interactions with MT binding proteins (MTBP) or by posttranslational modifications (PTMs) of tubulin. Polyglutamylation and tyrosination are two foremost PTMs that regulate the interaction between MTs and MTBPs, and play, therefore, a role in neurodegeneration. In this review, we summarise key information on tubulin PTMs in relation to AD and VaD and address the importance of studying further the tubulin code to reveal sites of potential intervention in development of novel and effective dementia therapy.